Adhesive Bacteria in the Terminal Ileum of Children Correlates With Increasing Th17 Cell Activation - Chen, Bo; Ye, Diya; Luo, Lingling; Liu, Weirong; Peng, Kerong; Shu, Xiaoli; Gu, Weizhong; Wang, Xiaojun; Xiang, Charlie; Jiang, Mizu (Frontiers in Pharmacology, 2020)
Humans and symbiotic bacteria are interdependent and co-evolved for millions of years. These bacteria communicate with human hosts in the gut in a contact-independent metabolite. Because most intestinal bacteria are non-adhesive, they do not penetrate the mucus layer and are not directly in contact with epithelial cells. (ECs). Here, we found that there are adhesive bacteria attached to the Children's terminal ileum. And we compared the immune factors of non- adhesive bacteria in the children ileum with adhesive bacteria as well. Stimulated Th17 cell associated with adherent bacteria in the ileum ECs. SIgA responses are similar to those roles in mouse experiments. Immunohistochemical analysis confirmed that the expression of SAA1, IL-2, IL-17A, foxp3, RORγt, TGFβ, and protein increased in Th17 cells. Finally, we used 16S rRNA genes 454 pyrosequencing to analyze the differences in bacterial communities between adhesive and non-adhesive bacteria in the ileum. Ileum with adherent bacteria demonstrated increased mucosa-related bacteria, such as Clostridium, Ruminococcus, Veillonella, Butyricimonas and Prevotella. We believe that adhesive bacteria in children’s terminal ileum associated with an increased Th17 cell activation and luminal secretory IgA. Adhesive bacteria very closely adhere to terminal ileum of children. They may play important role in human gut immunity and Crohn’s disease.